Điều kiện vận dụng mô hình PBIS trong hỗ trợ học sinh rối loạn phát triển học lớp 1 hòa nhập - Trần Thị Văn, Trần Thị Văn; Phạm Thị Trang, Phạm Thị Trang (Tạp chí Giáo dục, 2026)
Inclusive education for children with developmental disorders in Vietnam is mandated by law but faces numerous challenges due to insufficient training and support, limiting its effectiveness. This study identifies five key conditions for effectively applying the PBIS model to support first-grade students with developmental disorders in inclusive classrooms, including teacher capacity, multi-sector collaboration, adequate resources, data tracking systems, and supportive policies. Ensuring these conditions are in place is crucial for successful PBIS implementation, as it improves behavioral outcomes and inclusion of first-grade students with developmental disorders, contributing to a more inclusive and equitable educational environment.